Prognostic significance and therapeutic potential of the immune checkpoint VISTA in pancreatic cancer - Zelin Hou; Yu Pan; Qinglin Fei; Yali Lin; Yuanyuan Zhou; Ying Liu; Hongdan Guan; Xunbin Yu; Xianchao Lin; Fengchun Lu; Heguang Huang (2020)
Abstract Objective V-domain Ig suppressor of T cell activation (VISTA) is a novel immune checkpoint protein that belongs to the B7 family. The aim of this study was to investigate the prognostic significance and therapeutic potential of VISTA in patients with pancreatic cancer. Methods Using immunohistochemistry (IHC), we examined the expression of VISTA and demonstrated the associations between the VISTA and overall survival in 223 PDAC patients from 2 different unrelated retrospective cohorts. The multiplex immunofluorescence was performed to illuminate the relationship between VISTA expression and tumor-infiltrating immune cell subclusters of PDAC. We also verified the findings in The Cancer Genome Atlas (TCGA) dataset. The anti-tumor effect of anti-VISTA therapy was studied by the mouse model with liver metastases of PDAC. Results The VISTA protein was highly expressed in 25.6% of tumor cells (TCs), 38.1% of immune cells, and 26.0% of endothelial cells in 223 PDAC tumor tissues. VISTA expression in TCs was significantly associated with prolonged overall survival. Multiplex immunofluorescence analysis revealed that VISTA level was positively correlated with CD68 + macrophages, CD3 + T cells, and CD19 + B cells in PDAC. However, a higher expression level of VISTA was detected in tumor-infiltrating CD68 + macrophages than in CD3 + T and CD19 + B cells. Furthermore, anti-VISTA antibody treatment significantly reduced the number of metastatic nodules in livers of mouse models of PDAC with liver metastases. Conclusion VISTA expressed in TCs is associated with a favorable prognosis in PDAC. Moreover, immunotherapy with anti-VISTA antibodies may potentially be an effective treatment strategy against PDAC.